Assessing the relationship among corporate governance, sustainability disclosure and financial performance / Ng Yen Hong and Ong Tze San. - Ng, Yen Hong; Ong, Tze San (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2016)
Corporate governance is a monitoring mechanism that is created because of the possible conflict of interest that results from the separation of ownership and control between the shareholders and the board of directors. Control and procedures of companies can be improved given the introduction of corporate governance. Previous literature supports that corporate governance is an effective corporate governance that helps companies to increase the value of the firm, attract foreign investors, and improve quality of reporting. Previous studies also indicate that investors are drawn to companies that are actively involved in sustainability activities. However, real commitments from Malaysian companies for sustainable developments are questionable. This study identifies corporate governance mechanisms from agency theory perspective, in assessing its relationship to the financial performance, and sustainability disclosures. The theoretical contribution of this study is by the extension of previous studies by exploring the relationship and examining the mediating effect in sustainability disclosures between corporate governance and financial performance.